Z badań nad rozwojem ludności wiejskiej Pomorza Pruskiego w latach 1762-1775 : analiza taksonomiczna - Gazińska, Mirosława; Gaziński, Radosław (From Research on the Development of the Country-Folk of Prussian Pomerania Between 1762 and 1775 : the Taxonomical Analysis, 2008)
In the State Archive in Szczecin in the set "Manuscripts and Heritages" (Rękopisy i Spuścizny) there are eleven financial books from years 1762-1775 which concern Prussian Pomerania. They were used for conducting thorough research of the villages of Prussian Pomerania located in eighty territorial estate units (administrative districts, State-domains and municipal). The analysis deals among other with the restoration of the demographic potential after the seven years war. The research depicts the Pomeranian village in the second half of the XVIII century. Using simple taxonomical methods three homogeneous groups of the villages are distinguished.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 77-88